Use of population indices in cancer research: a scoping review - M. Courtney Hughes; Sadia Afrin; Mahdi Vaezi (International Society of Global Health, 2022)
# Background Population health indices measure a specific population group's health risk. There is a lack of research on how population indices are used in cancer research. The aim of this study was to provide the first scoping review of the literature on the use of population health indices in cancer research. # Methods A scoping review included three databases for research papers, which had to be published anytime through September 2021. PRISMA reporting guidelines were followed throughout this study, and the Mixed Methods Appraisal Tool was used to determine study quality. # Results A total of 1493 articles were identified, with 250 meeting the inclusion criteria. Population health indices are used in cancer research to explain the global and regional effects of intervention measures, such as cancer screening programs and policy implementation. Population health indices were also used to study cancer's economic outcomes, the burden of disease, and spatial and temporal patterns. Breast, lung, cervical, liver, and colorectal cancers appeared in most studies. Additionally, there is considerably less cancer research using population health indices in low-income and lower-middle-income countries. # Conclusions The use of population health indices for cancer research is widespread and can inform various investigations. There is a marked lack of such studies from low-income and lower-middle-income countries. Additionally, ensuring the accuracy and timeliness of data across all countries will improve the accuracy of the usefulness of population health indices.